A Wave Packet Evolution in the Field of One-Dimensional Potential - Khachatrian, A. Zh.; Panosyan, Zh. R.; Khachatryan, Zh. B.
A general theory for description of a wave packet evolution in the field of one-dimensional potential is developed. Based on the method of counter propagating waves it is shown that the evolving wave can be presented as a sum of three terms. The first one corresponds to the wave motion along the positive direction and the second one describes the wave motion along the negative direction. The third term defines the interference between the counter propagating waves. It is proofed that when the center of the carrier energy of the wave packet equals to the resonant tunneling energy then the motions of counter propagating waves separately take place.
Keywords: Physics; Field theory and polynomials; Quantum mechanics